Uncovering Key Themes and Future Directions in Therapeutic Garden Research: A Scientometric Approach - Amira Mas Ayu Amir Mustafa; Amirah Azzeri; Hafiz Jaafar; Mohd Iqbal Mohd Noor; N. H. Nik Ali; Zulkifli Halim; Zulkifli Mohamed (Malaysian Journal of Public Health Medicine (MJPHM), 2026)
Indexed by SCOPUS/MyCite